Primary manifestations of lymphomas in the orbit - Shenk, Yana; Jarosz, Bożena; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
We present two cases of patients with orbital lymphoma as a primary manifestation: 1) Rare, aggressive, diffuse large B-cell lymphoma. 2) The most common, low-grade orbital lymphoma originated from marginal zone or mucosa-associated lymphoid tissue (MALT), that underwent special diagnosis and treatment. This study is also to compare morphological changes in non-Hodgkin lymphomas with classical manifestations.